2014
DOI: 10.1002/chem.201403578
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Stabilization of Monomeric Antimony(I): A Carbene‐Supported Stibinidene

Abstract: A diamidocarbene was coordinated to an antimony(III) dichloride Lewis acid. Subsequent reduction with magnesium gave a monomeric, formally antimony(I) fragment that is supported by the diamidocarbene. Spectroscopic, crystallographic, and computational analyses demonstrated that the carbene ligand engages the antimony(I) center in π-backbonding resulting in a short (2.068(7) Å) Sb-C interaction that is comparable to those observed in known stibaalkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 66 publications
0
34
0
2
Order By: Relevance
“…As was reported for carbene‐stabilized pnictogenes, the 13 C NMR shifts of the carbene‐carbon atoms in 3 – 6 are shifted to higher fields compared to the starting carbene. [10b] The shifts observed for 3 – 6 are comparable to those reported by Bertrand et al and Hudnall et al for carbene‐stabilized stibinidenes , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As was reported for carbene‐stabilized pnictogenes, the 13 C NMR shifts of the carbene‐carbon atoms in 3 – 6 are shifted to higher fields compared to the starting carbene. [10b] The shifts observed for 3 – 6 are comparable to those reported by Bertrand et al and Hudnall et al for carbene‐stabilized stibinidenes , …”
Section: Resultsmentioning
confidence: 98%
“…Intramolecularly base‐stabilized pnictinidenes (type D ), and intermolecularly stabilized species containing strong σ‐donors such as N‐heterocyclic carbenes (NHCs, type A ), including IDipp‐PH and three NHC‐AsH derivatives [NHC = IDipp; IMes, IMes = 1,3‐bis(2,4,6‐trimethylphenyl)‐imidazol‐2‐ylidene]; IAr*, Ar* = 2,6‐CHPh 2 ‐4‐Me‐C 6 H 2 , and cyclic alkyl(amino)carbenes (CAACs, type B ), have been structurally characterized (Scheme ). However, the first intramolecularly (type D ) and intermolecularly (type B and C ) base‐stabilized stibinidenes were reported only recently, whereas transition metal‐coordinated stibinidenes are known for decades . Based on spectroscopic, crystallographic, and computational analyses, Hudnall et al concluded that DAC‐SbPh {DAC = Me 2 C[C(O)NMes] 2 C C } shows significant π‐backbonding contribution from the Sb I center to the carbene ligand, leading to a short Sb–C bond that is comparable to those observed in stibaalkenes .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, reactions with EBr 3 (E=Sb, Bi) gave simple IPr‐EBr 3 adducts, which do not undergo further Sb−Sb or Bi−Bi bond formation reactions . Finally, cAAC‐stabilized stibinidene cAAC‐SbCl was obtained by reduction of cAAC‐SbCl 3 with two equivalents of KC 8 , whereas the NHC‐stabilized phenylstibinidene was formed by reduction of NHC→SbCl 2 Ph with magnesium …”
Section: Resultsmentioning
confidence: 99%
“…DFT‐Rechnungen und EPR‐Daten haben gezeigt, dass, anders als beim Phosphoranalogon, die Spindichte nahezu ausschließlich am Antimonatom (90.7 %) lokalisiert ist. Eine Zwei‐Elektronen‐Reduktion von 66 ergibt das Lewis‐Base‐stabilisierte Chlorstibiniden 68 ; das zweite Beispiel eines monomeren Stibinidins, das außerhalb der Koordinationssphäre eines Übergangsmetalls stabil ist, wurde von Hudnall und Mitarbeitern durch Verwendung eines Diamidocarbens erhalten . Eine Drei‐Elektronen‐Reduktion führt zu einem zweiatomigen Antimonallotrop, das durch zwei Carbene überdacht ist ( 69 ).…”
Section: Caacs In Der Chemie Der Gruppe‐15‐elementeunclassified